Modulation of hepatocarcinoma cell morphology and activity by parylene-C coating on PDMS. - Nazaré Pereira-Rodrigues; Paul-Emile Poleni; Denis Guimard; Yasuhiko Arakawa; Yasuyuki Sakai; Teruo Fujii (PLoS ONE, 2010)
BACKGROUND: The ability to understand and locally control the morphogenesis of mammalian cells is a fundamental objective of cell and developmental biology as well as tissue engineering research. We present parylene-C (ParC) deposited on polydimethylsiloxane (PDMS) as a new substratum for in vitro advanced cell culture in the case of Human Hepatocarcinoma (HepG2) cells. PRINCIPAL FINDINGS: Our findings establish that the intrinsic properties of ParC-coated PDMS (ParC/PDMS) influence and modulate initial extracellular matrix (ECM; here, type-I collagen) surface architecture, as compared to non-coated PDMS substratum. Morphological changes induced by the presence of ParC on PDMS were shown to directly affect liver cell metabolic activity and the expression of transmembrane receptors implicated in cell adhesion and cell-cell interaction. These changes were characterized by atomic force microscopy (AFM), which elucidated differences in HepG2 cell adhesion, spreading, and reorganization into two- or three-dimensional structures by neosynthesis of ECM components. Local modulation of cell aggregation was successfully performed using ParC/PDMS micropatterns constructed by simple microfabrication. CONCLUSION/SIGNIFICANCE: We demonstrated for the first time the modulation of HepG2 cells' behavior in relation to the intrinsic physical properties of PDMS and ParC, enabling the local modulation of cell spreading in a 2D or 3D manner by simple microfabrication techniques. This work will provide promising insights into the development of cell-based platforms that have many applications in the field of in vitro liver tissue engineering, pharmacology and therapeutics.